2019
DOI: 10.1111/nph.15696
|View full text |Cite
|
Sign up to set email alerts
|

Advances and challenges in uncovering cold tolerance regulatory mechanisms in plants

Abstract: Contents SummaryI.IntroductionII.Cold stress and physiological responses in plantsIII.Sensing of cold signals in plantsIV.Messenger molecules involved in cold signal transductionV.Cold signal transduction in plantsVI.Conclusions and perspectivesAcknowledgementsReferences Summary Cold stress is a major environmental factor that seriously affects plant growth and development, and influences crop productivity. Plants have evolved a series of mechanisms that allow them to adapt to cold stress at both the physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
501
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 659 publications
(504 citation statements)
references
References 189 publications
(299 reference statements)
1
501
0
2
Order By: Relevance
“…Although a considerable portion of epigenetic variation correlates with trans‐acting genetic variants (Dubin et al ., 2016; Kawakatsu et al ., 2016), its nonrandom spatial distribution often exceeds the genetic structuring of natural populations. In addition, transcriptional rewiring through various epigenetic signals has been observed in plants upon multi‐generational exposure to abiotic stresses (Lämke & Bäurle, 2017), such as extreme temperatures (Ding et al , 2019; Friedrich et al , 2019), drought (Huang et al , 2019) and salinity (Yang & Guo, 2018). However, a dynamic interplay between specific genetic and epigenetic variants is commonly unravelled by studies of plant stress responses.…”
Section: Epigenetic Regulation Of Plant Responses To Abiotic Conditionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although a considerable portion of epigenetic variation correlates with trans‐acting genetic variants (Dubin et al ., 2016; Kawakatsu et al ., 2016), its nonrandom spatial distribution often exceeds the genetic structuring of natural populations. In addition, transcriptional rewiring through various epigenetic signals has been observed in plants upon multi‐generational exposure to abiotic stresses (Lämke & Bäurle, 2017), such as extreme temperatures (Ding et al , 2019; Friedrich et al , 2019), drought (Huang et al , 2019) and salinity (Yang & Guo, 2018). However, a dynamic interplay between specific genetic and epigenetic variants is commonly unravelled by studies of plant stress responses.…”
Section: Epigenetic Regulation Of Plant Responses To Abiotic Conditionsmentioning
confidence: 99%
“…Multilayered pathways to modulate gene expression have been indeed reported by Ding et al . (2019), this time for plants under cold stress, including regulation by post‐translational histone modifications and DNA methylation, but also by miRNAs and cold‐responsive long noncoding RNAs. A study focused on histone modifications in Brachypodium distachyon (Huan et al , 2018) reported vernalization‐induced, dose‐dependent epigenetic changes for multiple genes that coordinate various biological processes to prepare for floral transition.…”
Section: Epigenetic Regulation Of Plant Responses To Abiotic Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…A probable trigger for this change is a temperature-induced influx of calcium that is stored in the nuclear envelope and the nuclear reticulum (Bootman et al, 2009). Not only is calcium known to boost compaction of chromatin fibers (Phengchat et al, 2016) but calcium release channels are activated in a temperature-dependent manner, operating as thermo-sensors in both mammalian (Bautista et al, 2007) and plant cells (Ding et al, 2019).…”
Section: Discussionmentioning
confidence: 99%